KUALITAS AUDIT: AUDIT TENURE, BEBAN KERJA AUDITOR, ALIGNMENT DAN ENTRENCHMENT EFFECT - Destri Diana MD; Majidah Majidah (Jurnal Ilmiah MEA (Manajemen, Ekonomi, & Akuntansi), 2019)
This study aims to determine the effect of audit tenure (personal auditor), audit tenure (KAP), company age, auditor workload, alignment, and entrenchment effect on audit quality, both simultaneously and partially. Manufacturing companies listed on the Indonesia Stock Exchange in 2013-2016 are the object of research. Sampling technique with purposive sampling method obtained 64 companies with 256 samples. Data analysis using logistic regression analysis. The results showed that audit tenure (personal auditor), audit tenure (KAP), company age, auditor's workload, alignment, and entrenchment effect simultaneously influence audit quality. While partially, the age of the company has a positive effect on audit quality, and auditor workload has a positive effect on audit quality. The renewal of this research lies in the variable alignment effect and entrenchment effect. Recommendations for: (1) Further research can conduct research in different industries by not including variables that have no effect on this study; (2) Companies can consider the auditor's workload as one of the criteria in choosing a qualified auditor; (3) For professional organizations (IAI and IAPI) auditor workload is expected to be an input for improving regulations related to audit quality.